Pengaruh Model Pembelajaran Team Games Tournament (TGT) Terhadap Hasil Belajar Siswa Kelas IV Pada Tema 3 Subtema 1 Di UPTD SD Negeri 122379 Pematang Siantar - Novriyanti Saragih; MinarTrisnawati Tobing; Esti Marlina Sirait (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine: The influence of the Team Games Tournament (TGT) learning model on the learning outcomes of class IV students in theme 3 subtheme 1 at UPTD SD Negeri 122379 Pematang Siantar. The type of research used in this research is quantitative research. The research design used in this research is experimental, with a pre-experimental design that uses a one group pretest posttest design. The sample in this research was class IV UPTD SD Negeri 122379 Pematang Siantar, totaling 20 students. The instrument used in this research was a written test in the form of multiple choices.The results of hypothesis testing in this research are that there is a significant influence obtained from data analysis. This can be seen from the data analysis of pretest (55.8) and posttest (83.6) scores. From the results of the hypothesis test, with a significance level of α = 0.05, it can be seen that the t test results obtained are t_count of 13.256 and t_table of 2.093 with a significance level of α = 0.05. Thus t_count 〖>t〗_table which means H0 is rejected and Ha is accepted. Based on the results of the analysis, it can be concluded that there is an influence of the use of the Team Games Tournament (TGT) learning model on the learning outcomes of class IV students in Theme 3 Subtheme 1 at UPTD SD Negeri 122379 Pematang Siantar.